2017
DOI: 10.1002/jat.3488
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine exacerbates ketamine toxicity in zebrafish: Mechanistic studies on drug–drug interaction

Abstract: Cyclosporine A (CsA) is an immunosuppressive drug commonly used in organ transplant patients to prevent allograft rejections. Ketamine is a pediatric anesthetic that noncompetitively inhibits the calcium-permeable N-methyl-D-aspartic acid receptors. Adverse drug-drug interaction effects between ketamine and CsA have been reported in mammals and humans. However, the mechanism of such drug-drug interaction is unclear. We have previously reported adverse effects of combination drugs, such as verapamil/ketamine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…Ketamine (2.0 mM) treatment continued for 20 h (static exposures) in the presence or absence of ALCAR (1.0 mM). In our previous studies, these specific concentrations of ketamine and ALCAR for the specific time of exposure were found to be effective in inducing detectable toxicities and their amelioration, respectively (Kanungo et al, 2012; Robinson et al, 2017). Previously, we have shown that the amount of ketamine accumulation (~8 μM) in the zebrafish embryos/larvae treated with 2 mM is closer to the lower range of human anesthetic range (plasma concentration) (Trickler et al, 2013).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Ketamine (2.0 mM) treatment continued for 20 h (static exposures) in the presence or absence of ALCAR (1.0 mM). In our previous studies, these specific concentrations of ketamine and ALCAR for the specific time of exposure were found to be effective in inducing detectable toxicities and their amelioration, respectively (Kanungo et al, 2012; Robinson et al, 2017). Previously, we have shown that the amount of ketamine accumulation (~8 μM) in the zebrafish embryos/larvae treated with 2 mM is closer to the lower range of human anesthetic range (plasma concentration) (Trickler et al, 2013).…”
Section: Methodsmentioning
confidence: 89%
“…Ketamine-induced cardiac dysfunction has been reported in human fetus (Saarenmaa et al, 2001), infant non-human primates (Hotchkiss et al, 2007), Xenopus (Guo et al, 2016) and zebrafish (Guo et al, 2017; Kanungo et al, 2012; Robinson et al, 2017). Ketamine can affect the right ventricular function and pulmonary artery pressure since it increases pulmonary vascular resistance (Craven, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was difficult to determine what effects ketamine and NAC have on those cells. We have previously shown functional evidence that ALCAR’s ability to open L-type calcium channels could be at play to compensate for ketamine’s blockade of calcium-permeable NMDA receptors, especially during prolonged exposures [8,19,25]. Interestingly, NAC has been shown to increase intracellular calcium [22].…”
Section: Discussionmentioning
confidence: 99%
“…For treatment with ketamine and NAC, 28 hpf embryos were used since our previous studies showed that these embryos as whole organisms respond to ketamine anesthesia [8,18] and ketamine exposure at the gastrula stage leads to non-specific effects [25]. For each experiment that analyzed all the endpoints, eggs laid at the same time from several females were pooled.…”
Section: Methodsmentioning
confidence: 99%